Privacidade e ética na sociedade de dados: uma reflexão filosófica sobre a Lei Geral de Proteção de Dados brasileira - Canedo, Fabiolla Labelle Ornelas (2021)
This paper aims to study the main transformations of the digital age, which have been taking place in society exponentially, resulting from the technological revolution, as well as to analyze the impacts and challenges for law in the so-called "data society", reflecting that so the great technological forces are shaping the world, and influencing the future of man, economy, social relations, and the entire planet. It seeks to create conjectures about the main technologies driving digital transformation, especially Big Data and Artificial Intelligence, reflecting on the role of law in the control and regulation of the use of these new technologies, ensuring that they are always handled in the light of ethics and justice. The study seeks to analyze the rise of the right to the protection of personal data in Brazil and worldwide, and to observe the effectiveness of the Brazilian General Data Protection Law, as an instrument to guarantee fundamental rights, especially privacy, equality and freedom, essential to maintenance of the democratic rule of law